Response to therapy in Richter syndrome: a systematic review with meta-analysis of early clinical trials - Sousa-Pimenta, Mário; Martins, Ângelo; Mariz, José Mário; Berraondo, Pedro (Frontiers in Immunology, 2023)
Richter syndrome (RS) represents the clonal evolution of chronic lymphocytic leukemia with histological transformation into a high-grade B cell lymphoma (diffuse large B cell lymphoma -DLBCL) or Hodgkin lymphoma. Considering that RS is an uncommon condition with poor prognosis, few high-quality evidence is available. To overcome this unmet need, this meta-analysis aimed to pool efficacy of early clinical trials in Richter syndrome (DLBCL subtype). Methods: MEDLINE, Scopus and Web of Science were searched up to May of 2023 to identify clinical trials decoying efficacy. The pooled complete response, objective response and intension-to-treat failure rates were calculated by pharmacological categories (classical chemotherapy, immunochemotherapy, immunotherapy, Brutontyrosine kinase inhibitors, targeted approaches, cell-based therapies and combinatorial regimens) using the Der-Simonian and Laird random-effects model. The Freeman-Tukey double arcsine method was used to estimate variance and confidence intervals. Heterogeneity was assessed using the I 2 method. Results: Overall, from 1242 studies identified, 30 were included, pooling data from 509 patients. The higher efficacy rates when, cell-based therapies were excluded, were achieved by immunochemotherapeutic regimens followed by combinatorial regimens, with complete response rates of 21.54% (IC95%14. , respectively. Bispecific antibodies (alone or coupled with a chemotherapy debulking strategy) overtook Bruton tyrosine kinase inhibitors response rates. The latter, although achieving objective response rates above average, presented scarce complete response rates. Checkpoint inhibitors alone usually do not lead to complete responses, but their effectiveness may improve when combined with other agents, unveiling the importance of immune microenvironmental modulation. Conclusion: This is the first meta-analysis of early clinical trials assessing the impact of different therapeutics in RS. By analyzing the pooled efficacy estimates, our work suggests the role of a tailor-made bridging therapy for young patients with RS eligible for allogeneic hematopoietic stem cell transplantation, formally the only curative strategy.